Conventional weight loss interventions across the different BMI obesity classes: A systematic review and quantitative comparative analysis. (3rd May 2020) - Bauer, Kerstin; Lau, Teresa; Schwille‐Kiuntke, Juliane; Schild, Sandra; Hauner, Hans; Stengel, Andreas; Zipfel, Stephan; Mack, Isabelle
Abstract: Objective: The recommendation for conventional body weight loss (BWL) treatment in obesity is 5–10%. It is not clear whether BWL is similar across the three different body mass index (BMI) obesity classes. The aim was to provide an overview on BWL across these classes in moderate lifestyle/diet intervention programs. Method: A systematic literature search was conducted and the evidence of randomized controlled trials (RCTs) and pre‐post design studies synthesized. The outcome was BWL. Results: For RCTs, mean BWL in the intervention group was 3.6 kg (class I) and 5.3 kg (class II), which equates to 4 and 5% BWL, respectively. None of the assessed class III obesity studies met the inclusion criteria. For pre‐post design studies, mean BWL was 5.4 kg (class I), 5.5 kg (class II) and 7.9 kg (class III), with high variation within and across studies in the latter. This equates to 6, 5 and, 6% BWL, respectively. Conclusions: BWL of moderate BWL programs are similar across the different obesity classes. For class I obesity, the results differ between RCT and pre‐post design studies by 2% BWL. The high variation of BWL in class III obesity might reflect different states of motivation such as the attitude towards bariatric surgery.